2014
DOI: 10.14429/djlit.34.6.8043
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Librarianship—New Horizon of Librarianship

Abstract: This paper is an effort to understand meaning of embedded librarianship, and its implementation in academic libraries and how is it useful to the users. It attempts to understand the terminology and has included an expert opinion on the subject. It explores the core competency and skills and attributes an embedded librarian should possess. The paper is based on primary and secondary sources which also deal with brief discussion of the charactersitcs of embedded librarianship and is an attempt to empirically hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Abrizah et al (2016), found while reviewing related literatures, "embedded librarians play a vital role in providing support in online learning, teaching information literacy, managing and providing access to information resources in the classrooms, assisting in research and other scholarly communication activities". "Under the paradigm of embedded librarianship, professionals should perform key role of co-teachers and co-researchers, and achieve the trustworthiness between faculty and library" (Talwar, 2014). Browler and Street (2008) in their research, noticed that the students' performance was getting better in comparison to that phase, when no librarian was embedded in the course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abrizah et al (2016), found while reviewing related literatures, "embedded librarians play a vital role in providing support in online learning, teaching information literacy, managing and providing access to information resources in the classrooms, assisting in research and other scholarly communication activities". "Under the paradigm of embedded librarianship, professionals should perform key role of co-teachers and co-researchers, and achieve the trustworthiness between faculty and library" (Talwar, 2014). Browler and Street (2008) in their research, noticed that the students' performance was getting better in comparison to that phase, when no librarian was embedded in the course.…”
Section: Discussionmentioning
confidence: 99%
“…Shumaker and Talley observed in their report, prepared under the Special Libraries Association Research Grant ( 2007), commonly, "embedded librarianship programmes start by shifting the location of delivery, not changing the nature of the service itself". "When the libraries are transforming into knowledge powerhouses, the roles of librarians are also revamping and reshaping" (Talwar, 2014). For carrying out a successful embedded librarianship model, it needs a high level of enthusiasm, a great knowledge base or access to one and flexibility to adapt.…”
Section: Prerequisites For Practicing Embedded Librarianshipmentioning
confidence: 99%
“…Thus, they must be careful enough to reposition themselves along with demonstrating library values to the academic community. Promoting RMTs is a kind of embedded librarianship 26 . Librarians have been regarded as a specialist in the management of citations and we have also been promoting ourselves as being so and as such it is up to us how we relate RMTs to the traditional reference management system and show the benefit over the later.…”
Section: Librarians' Role In Pramoting Rmts 81 Why Librarians Should Promote Rmtsmentioning
confidence: 99%
“…Talwar describes an environment of shared contribution that helps build relationships between the users and embedded librarians. As trust and understanding develops Talwar (2014) states that, "The embedded librarian becomes just as engaged in the work of the team as any other team member. "…”
Section: Embeddedmentioning
confidence: 99%